1972
DOI: 10.1139/v72-606
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation and Decarboxylation of Tyrosine Studied by E.P.R. and C.I.D.N.P. Techniques

Abstract: The photooxidation of deoxygenated solutions of tyrosine in water at pH 8.5–12.6 has been studied at room temperature using e.p.r. spectroscopy. By means of e.p.r., four radicals were detected during irradiation with the full spectrum of a Hg–Xe arc lamp. These were identified as the tyrosyl radical, [Formula: see text] and two radicals derived from dopa. A tentative mechanism suggested for [Formula: see text] formation involves the reaction of tyrosine with the hydrated electron, which has been ejected from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 0 publications
3
38
0
Order By: Relevance
“…The 19 F hyperfine coupling constant computed for the 3-fluorotyrosyl radical is +1.57 mT ( Table 1) as opposed to )0.65 mT for the corresponding proton in the tyrosyl radical [21]. For non-viscous solutions and in a strong magnetic field, the geminate CIDNP effect of a particular nucleus is proportional to its hyperfine coupling constant in the intermediate radical [11].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The 19 F hyperfine coupling constant computed for the 3-fluorotyrosyl radical is +1.57 mT ( Table 1) as opposed to )0.65 mT for the corresponding proton in the tyrosyl radical [21]. For non-viscous solutions and in a strong magnetic field, the geminate CIDNP effect of a particular nucleus is proportional to its hyperfine coupling constant in the intermediate radical [11].…”
Section: Discussionmentioning
confidence: 94%
“…The relatively inexpensive Hartree-Fock-based computation of the shielding tensor was used because previous studies had revealed no obvious advantage of MP2 or DFT based methods for the 19 F nuclei of the molecules in question [20]. The calculated hyperfine couplings for the neutral radicals derived from tyrosine and 3-fluorotyrosine by abstraction of hydrogen from the phenolic OH group are given in Table 1 together with the experimental values for the tyrosyl radical [21].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conseq~~e n t l y it would appear that the exchangeable hydrogen is attached to an oxygen atom. Furthermore, the hydrated electron most likely would add to the carbonyl group at position 1. to the C0,-group of tyrosine (14). These BiOphys.…”
Section: Structure and Mechanismmentioning
confidence: 92%
“…The absence of polarized water can be due to both the known fact that the AcTyr radical cation loses proton already at times characteristic of geminal processes and the absence of functional groups that can exchange with water with noticeable HFI constants. 32 In fact, the CIDNP effects of N acetyltyrosine correspond to the spin density distribution in the free radical rather than in the radical cation as in the case of N acetyl tryptophan, because the ratio of CIDNP intensities ob served for the ortho and meta protons is 3.5 instead of 7.0 expected for the radical cation. 10,32 It should be noted that the earlier observed and described CIDNP effects in redox photoprocesses involving tyrosine were also ascribed to the pair of the neutral tyrosine and substrate radicals.…”
Section: Methodsmentioning
confidence: 99%